2008
DOI: 10.1084/jem.20070679
|View full text |Cite
|
Sign up to set email alerts
|

RAGE signaling sustains inflammation and promotes tumor development

Abstract: A broad range of experimental and clinical evidence has highlighted the central role of chronic infl ammation in promoting tumor development. However, the molecular mechanisms converting a transient infl ammatory tissue reaction into a tumor-promoting microenvironment remain largely elusive. We show that mice defi cient for the receptor for advanced glycation end-products (RAGE) are resistant to DMBA/TPA-induced skin carcinogenesis and exhibit a severe defect in sustaining infl ammation during the promotion ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
296
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 344 publications
(317 citation statements)
references
References 37 publications
10
296
1
4
Order By: Relevance
“…It is known that S100A8/A9 binds to RAGE and TLR4 (18,19). Our flow cytometry data indicated that murine NK cells expressed RAGE, but not TLR4, on their surface (Fig.…”
Section: S100a8/a9 Activated Nk Cells Through Ragementioning
confidence: 59%
“…It is known that S100A8/A9 binds to RAGE and TLR4 (18,19). Our flow cytometry data indicated that murine NK cells expressed RAGE, but not TLR4, on their surface (Fig.…”
Section: S100a8/a9 Activated Nk Cells Through Ragementioning
confidence: 59%
“…The S100A12 protein has a number of different target proteins, such as the pattern recognition receptor RAGE (receptor for advanced glycation end products)125, 126 and plays a central role in the innate and acquired immune response 113, 127…”
Section: Biomarkers In Chronic Inflammatory Enteropathies Of Dogsmentioning
confidence: 99%
“…Quantitative real-time polymerase chain reaction (RQ-PCR) analysis was performed as described previously. 16 Primers used for RQ-PCR analysis are listed in Supporting Table 2. Target gene cycle of threshold values were normalized to the corresponding cycle of threshold values of Hprt (for mouse samples) or LAMINB1 (for human samples) using the change in cycle of threshold method.…”
Section: Animalsmentioning
confidence: 99%